Temperature Dependent Control of the R27 Conjugative Plasmid Genes - Gibert, Marta; Paytubi, Sonia; Madrid, Cristina; Balsalobre, Carlos (Frontiers in Molecular Biosciences, 2020)
Conjugation of R27 plasmid is thermoregulated, being promoted at 25°C and repressed at 37°C. Previous studies identified plasmid-encoded regulators, HtdA, TrhR and TrhY, that control expression of conjugation-related genes (tra). Moreover, the nucleoid-associated protein H-NS represses conjugation at non-permissive temperature. A transcriptomic approach has been used to characterize the effect of temperature on the expression of the 205 R27 genes. Many of the 35 tra genes, directly involved in plasmid-conjugation, were upregulated at 25°C. However, the majority of the non-tra R27 genes—many of them with unknown function—were more actively expressed at 37°C. The role of HtdA, a regulator that causes repression of the R27 conjugation by counteracting TrhR/TrhY mediated activation of tra genes, has been investigated. Most of the R27 genes are severely derepressed at 25°C in an htdA mutant, suggesting that HtdA is involved also in the repression of R27 genes other than the tra genes. Interestingly, the effect of htdA mutation was abolished at non-permissive temperature, indicating that the HtdA-TrhR/TrhY regulatory circuit mediates the environmental regulation of R27 gene expression. The role of H-NS in the proposed model is discussed.